Non-coding RNA and autophagy: Finding novel ways to improve the diagnostic management of bladder cancer - Tantray, Ishaq; Ojha, Rani; Sharma, Aditya P. (Frontiers in Genetics, 2023)
Major fraction of the human genome is transcribed in to the RNA but is not translated in to any specific functional protein. These transcribed but not translated RNA molecules are called as non-coding RNA (ncRNA). There are thousands of different ncRNAs present inside the cells, each regulating different cellular pathway/pathways. Over the last few decades ncRNAs have been found to be involved in various diseases including cancer. NcRNAs are reported to function both as tumor enhancer and/or tumor suppressor in almost each type of cancer. Urothelial carcinoma of the urinary bladder is the second most common urogenital malignancy in the world. Over the last few decades, ncRNAs were demonstrated to be linked with bladder cancer progression by modulating different signaling pathways and cellular processes such as autophagy, metastasis, drug resistance and tumor proliferation. Due to the heterogeneity of bladder cancer cells more in-depth molecular characterization is needed to identify new diagnostic and treatment options. This review emphasizes the current findings on ncRNAs and their relationship with various oncological processes such as autophagy, and their applicability to the pathophysiology of bladder cancer. This may offer an understanding of evolving ncRNA-targeted diagnostic tools and new therapeutic approaches for bladder cancer management in the future.